The Paulista Curriculum as a tool and a resource for teacher planning to climate change education - Resende de Faria, Daniela (2023)
The objective of this study was to analyze the theme "Climate Change" in the Paulista Curriculum (CP), verifying the suggestions about the teaching and learning proposals. To do so, the content analysis of the CP was used to investigate the key term "Climate Change" as well as related keywords. These were divided into 5 sets, from which we highlight set 1, concentrated in the area of Human and Applied Social Sciences and Nature Sciences and their Technologies, in the curricular components of Geography and Biology, in the 1st grade, showing the tendency to connect the theme to Environmental Education. It is understood that this can generate fragmentation and a sense of finitude, reinforcing the need to seek didactic-pedagogical proposals that enable education on climate change to be worked throughout the MS and by more areas/curricular components.